Anatomy as a Model Environment for Acquiring Professional Competencies in Medicine: Experiences at Harvard Medical School. Issue 2 (7th August 2020) - McDaniel, Katherine G.; Brown, Taylor; Radford, Caitlin C.; McDermott, Cynthia H.; van Houten, Trudy; Katz, Martha E.; Stearns, Dana A.; Hildebrandt, Sabine
Abstract : Anatomy education provides students with opportunities to learn structure and function of the human body, to acquire professional competencies such as teamwork, interpersonal skills, self‐awareness, and to reflect on and practice medical ethics. The fulfillment of this wide potential can present challenges in courses that are part of an integrated curriculum and shorter than traditional courses. This new reality, together with students' increasing concern about the stresses within medical education, led to efforts at Harvard Medical School to implement practical steps toward an optimal learning environment in anatomy. These were based on core elements of ethical anatomy education and principles of trauma‐informed care. Anatomy is conceptualized here as the "first clinical discipline, " with relational interactions between anatomical educators, medical students, and body donors/patients. Essential prerequisites for the implementation of this work were support by the medical school leadership, open partnership between engaged students and faculty, faculty coordination, and peer‐teaching. Specific interventions included pre‐course faculty development on course philosophy and invitations to students to share their thoughts on anatomy. Student responses were integrated in course introductions, combined with a pre‐dissection laboratory visit, an introductory guide, and a module on the history and ethics of anatomy. During the course, team‐building activities were scheduled, and self‐reflection encouraged, for example, through written exercises, and elective life‐body drawing. Students' responses to the interventions were overall positive, but need further evaluation. This first attempt of a systematic implementation of an optimal learning environment in anatomy led to the identification of areas in need of adjustment.